Owners’ informed consent for a necropsy of a companion animal as a conflict-reducing mean in the veterinary practice - Andrzej Dzikowski; Ireneusz Sołtyszewski; Mariusz Z. Felsmann; Justyna Karaźniewicz; Beata Kosiba; Józef Szarek (Journal of Modern Science, 2021)
Objectives The authors’ aim is not only to extend research, but also to assist in problem-solving actions in every-day veterinary practice.